HE4 and CA-125 kinetics to predict outcome in patients with recurrent epithelial ovarian carcinoma: the META4 clinical trial - Fabbro, Michel; Lamy, Pierre-Jean; Touraine, Célia; Floquet, Anne; Ray-Coquard, Isabelle; Mollevi, Caroline (Frontiers in Oncology, 2024)
HE4 and CA-125 are used for epithelial ovarian cancer (EOC) screening, diagnosis, and follow-up. Our objective was to study HE4 and CA-125 kinetics in patients treated for recurrent EOC. Serum samples were prospectively collected before the first chemotherapy cycle and every 3 months until disease progression. Data from 89/101 patients could be analyzed. At baseline, the median CA-125 and HE4 concentrations were 210 IU/L (7–10,310) and 184 pM (31–4,836). Among the 12 patients (13%) with normal CA-125 (<35 IU/L) concentration, eight had HE4 concentration ≥75 pM, and among the 16 patients with normal HE4 concentration (18%), 12 had increased CA-125 concentration. The median nadir concentrations were 31 IU/L (3–8,744) for CA-125 and 75 pM (20–4,836) for HE4. The median times to nadir were 14 (0–130) weeks for CA-125 and 12 (0–52) weeks for HE4. In multivariate analysis, CA-125 and HE4 nadir concentrations (<35 IU/L, HR 0.35, 95% CI: 0.17–0.72 and<75 pM, HR 0.40, 95% CI: 0.20–0.79) and time to CA-125 and HE4 nadir (>14 weeks, HR 0.37, 95% CI: 0.20–0.70 and >12 weeks, HR 0.43, 95% CI: 0.23–0.83) were prognostic factors of progression-free survival. More investigations on HE4 kinetics could help to better monitor patients with CA-125 concentration within normal values.